Suppressing disc brake squeal through structural modifications - Saw, Chun Lin; Abu Bakar, Abd. Rahim; Wan Harujan, Wan Mohd. Musyris; Abd. Ghani, Badri; Jamaluddin, Mohd. Rahimi (Faculty of Mechanical Engineering, 2009)
Brakes squeal remains an elusive problem in the automotive industry. There have been many proposals proposed to tackle these problems but very few are effective to suppress and eliminate it. This paper proposes a solution to suppress disc brake using the finite element method. First a three dimensional finite element (FE) model of a real disc brake assembly is developed and validated. Then, complex eigenvalue analysis made available in commercial FE software package is performed to determine stability of the brake system where positive real parts of the complex eigenvalue indicate unstable system and in turn exhibit squeal generation in the brake assembly. Then, various disc modifications are proposed to reduce the brake squeal. A good modification should be able to reduce and eliminate squeal at various brake operating conditions